A Descriptive Exploratory Study of the Causes and Effects of Hypertension Among Ghanaian Soldiers and Their Families. (October 2022) - Dartey, Anita Fafa; Lasidji, Berlinda Narh; Baku, Elizabeth; Worna Lotse, Comfort; Kuug, Anthony Kolsabilik; Dzansi, Gladys
Introduction: The quality of life of any soldier can be affected by a simple diagnosis of Hypertension. Hypertension has not been directly linked to a single cause; however, knowing the associated risks and early diagnosis can help with its management. This study aimed to explore and describe the causes of hypertension among soldiers and its effects on their families. Objective(s): To explore and describe the causes of hypertension and its effects on soldiers and their families. Methods: A qualitative technique and an exploratory descriptive design were used in this study. At saturation, a total of 10 soldiers were face-to-face interviewed and gathered data simultaneously transcribed and subjected to a content analytic method of analysis. Participants approved being audio recorded on tape with an audio recording device. Results: Effects of hypertension on personal lives of soldiers, effects of hypertension on family life, and effects of hypertension on social life were identified as the causes and risk factors of hypertension among the soldiers. These themes are further expanded by their subthemes in the areas of decreased physical activity including sex life, decrease interaction with family, and isolation from friends. Conclusion: This study revealed that hypertension does have effects on one's personal life, family life, and social life. Hence, it is recommended that frequent health education on hypertension and its effects should be organized in the various Garrisons by the public health department for all soldiers and their families. Screening programs should be organized for early hypertension detection. Soldiers should be educated on appropriate eating habits, weight and financial management, and reduction in tobacco and alcohol.